Assessing Impact of Sociodemographic, Clinical, and Facility Characteristics on Survival after T1 Laryngeal Cancer Treatment. (2nd September 2014) - Misono, Stephanie; Marmor, Schelomo; Yueh, Bevan; Virnig, Beth A.
Abstract : Objectives: Prior work identified differences in survival by treatment type for localized laryngeal squamous cell carcinoma (LSCC) in the Surveillance Epidemiology and End Results (SEER) registries. We sought to determine whether these differences were attributable to sociodemographic, clinical, and treatment facility characteristics in the elderly. Methods: The SEER‐Medicare linked files (1991‐2009) identified patients (ages 66+ years) with T1 LSCC. Logistic regression models were constructed to identify sociodemographic characteristics associated with treatment type. Kaplan‐Meier methods were used to examine the association of treatment type and survival. Cox proportional hazards modeling was used to assess the impact of potentially important factors such as sociodemographic, clinical, or facility characteristics. Results: We identified 1369 patients with T1 LSSC. Radiation alone was the most common treatment. Treatment with local surgery ± radiation was associated with slightly better survival than treatment with radiation alone in our unadjusted Kaplan Meier model. Adjusted for comorbidity, treatment with both local surgery and radiation was associated with greater survival ( P =. 002) than treatment with local surgery or radiation alone. No significant association was observed between sociodemographic factors (income and urban/rural location) or facility characteristics (hospital size or volume) and hazard of death. Conclusions: Previously observed differences in survival across single modality treatment types for T1 LSSC in the elderly may be partially attributable to medical comorbidity, but treatment with both surgery and radiation was associated with improved survival independent of comorbidity. Other patient and facility characteristics showed no appreciable impact on survival after treatment of T1 LSSC in this population.